JUS BUAH BERBASIS BIT MERAH (Beta vulgaris) PENAMBAHAN NANAS SMOOTH CAYENNE (Ananas comosus (L) merr.) SEBAGAI PANGAN FUNGSIONAL BAGI PENDERITA HIPERTENSI - Safarotul Magfiroh; Maryam Razak (Fakultas Pertanian Universitas Yudharta Pasuruan, 2019)
Hypertension is an increase in systolic blood pressure, the height of which depends on the age of the individual affected. Red beet (Beta vulgaris) is one of the vegetables rich in inorganic nitrate, betalain, folic acid, riboflavin and potassium antioxidant compounds. Potassium and folic acid play an important role in the process of regulating blood pressure. The addition of pineapple aims to reduce the smell of the soil in red beets. In addition, pineapple also contains potassium and vitamin C which can help lower blood pressure. The purpose of this study was to determine the organoleptic quality, potassium levels and antioxidant activity of red beet juice (Beta vulgaris) by adding smooth cayenne pineapple (Ananas comosus (L) merr.) To patients with hypertension. This research is a RAL study (Completely Randomized Design) with three levels of treatment, namely the ratio of red bits to pineapple, P1 (100: 37.5), P2 (100: 50) and P3 (100: 62.5). Organoleptic quality analysis descriptively and Kruskal Wallis with Mann Whitney follow-up. Potassium test using the Spectometry test and the antioxidant activity test using DPPH Spectometry and converted to IC50. Chemical quality analysis using One-way ANOVA with Duncan's Multiple Range Test. The results showed that the addition of smooth cayenne pineapple had a significant influence on the quality of organoleptic juices. The panelists' acceptance of organoleptic quality of juice (smell, taste and color) tends to be favored. The level of potassium juice increased by an average of 468-1128 mg/ 100ml, the antioxidant juice activity on average was weak to moderate (166.9-101.4 µg/ml). The best treatment level is P3. Further research is needed on the use of pineapple humps, to increase antioxidant levels, and the addition of pineapple or other types of fruit is needed to increase the acceptability of juice.